DORAEMON AS SYMBOL OF JAPANESE 2008 CULTURAL DIPLOMACY IN INDONESIA - Diah Kusuma.W (2009)
ABSTRACT Conventional, sense of diplomacy is an attempt of a nation-state to pursue national interests in international society. if in the past the affectivity of diplomacy need political support ir economic or military power, but now economy if the macro understanding of this culture must be linked to cultural diplomacy, cultural diplomacy the fact is the only kind of diplomacy that humans possess. Diplomacy for any man does, whether it is economic diplomacy, military and others, including as